INTERNALIZATION OF ISLAMIC VALUES IN THE MILLENNIAL GENERATION THROUGH SOCIAL MEDIAInternalization Of Islamic Values In The Millennial Generation Through Social Media - Bahyati, Bahyati; Fitriya, Fitriya; Silviyah, Silviyah; Mauludin, Dindi; Inayah, Bidayatul (The Magister of Islamic Education IAIN Pontianak, 2025)
Technological developments have a big influence on society. One form of technology used by society is the internet. Social media that is used well and usefully can be used as material to increase knowledge. This research aims to analyze the application and internalization of Islamic values ??among the millennial generation in Indonesia, especially through the use of social media and digital applications such as WhatsApp. The process of internalizing Islamic values ??among millennials is identified through contemporary religious education, the use of social media to spread Islamic teachings, community activities involving social discussions, and attitudes of tolerance towards diversity. The research results show that Islamic religious education which integrates social and global issues plays a very important role in shaping the character of the millennial generation. Social media, especially WhatsApp, is used as a platform to share Islamic information and discuss Islamic teachings in everyday life. In addition, the millennial generation tends to be open to religious and cultural differences, which facilitates a more inclusive acceptance of Islamic values.